Estudio del Trabajo en el área de producción de quesos de la empresa Lácteos La Copa. - López Galarza, Marcelo Efraín (2024)
ABSTRACT: The main objective of this research work is to carry out a study of the work in the production area of the company "Lácteos La Copa", considering that one of the main problems is its poor organization, order and cleanliness. The application of work study techniques and tools help improve the production process. Hence, the company's production processes were analyzed and unproductive times were determined during the production of: fresh cheese, mozzarella and Andean oregano cheese. Then we proceed to improve the methods within the company, in order to begin the process of taking samples that will first help us calculate the number of observations necessary for the study of the work; carry out the time study and prepare the analytical and route diagrams of the company “Lácteos La Copa”. The results show that unproductive times differ between cheese production processes, due to the activities carried out within each of the processes. In conclusion, to reduce unproductive times generated by the company, it is necessary to implement a Procedures Manual that clearly and in detail guides the stages of each process, this will ensure standardization, product quality and operational efficiency. Documenting the processes will allow you to eliminate unnecessary movements, reduce unproductive times and optimize resources, increasing productivity and reducing production costs.